Combining In Vitro, In Vivo, and In Silico Approaches to Explore the Effect of Ceratonia siliqua and Ocimum basilicum Rich Phenolic Formula on Lipid Metabolism and Plasma Lipoprotein Oxidation in Mice Fed a High-Fat Diet: A Follow-Up Study - Mohammadine Moumou; Amani Tayebi; Abderrahmane Hadini; Omar M. Noman; Abdulsalam Alhalmi; Hamza Ahmoda; Souliman Amrani; Hicham Harnafi (Metabolites)
Background/Objectives: Hyperlipidemia is a serious risk factor for cardiovascular diseases and liver steatosis. In this work, we explored the effect of an herbal formula (CBF) containing immature Ceratonia siliqua pods and Ocimum basilicum extracts on lipid metabolism disorders and lipoprotein-rich plasma (LRP) oxidation in mice. Methods: The phenolic composition was determined using HPLC-DAD analysis. The antioxidant activity was studied using various in vitro methods. Acute toxicity was evaluated in mice. Importantly, the effect of the CBF on lipid metabolism disorders was investigated in a high-fat diet (HFD) hyperlipidemia mouse model. An in silico study was carried out to predict underlying mechanisms. Results: The HPLC analysis revealed gallic acid, cinnamic acid, and naringenin as major phenolics of the carob pod aqueous extract. Concerning the basil hydro-ethanolic extract, rosmarinic, chicoric, caftaric, and caffeic acids were the main phenolics. Accordingly, the CBF prevented LRP oxidation in a concentration-dependent manner. This formula is not toxic in mice (LD50 > 2000 mg/kg body weight). Moreover, animals administered the CBF at 200 mg/kg/day presented a significant decline in their body weight gain, adipose tissue weight, plasma total cholesterol, low-density lipoprotein cholesterol (LDL-C) level, and glycaemia after 10 weeks’ treatment. Accordingly, the CBF decreased the plasma atherogenic index and the LDL-C to HDL-C ratio and reduced the level of fats accumulated in the liver. The molecular docking study revealed that chicoric, rosmarinic, and caftaric acids, and naringenin bound particularly strongly to many proteins involved in the regulation of lipid and cholesterol metabolism. This includes the HMG-CoA reductase, PPARα/γ, PCSK9, Cyp7a1, and ATP-citrate lyase. Conclusions: The CBF could be a good source of natural supplements, functional foods, and pharmaceuticals effective in managing hyperlipidemia and oxidative stress and preventing their related cardiovascular disorders.